Resource Capacity of Academic Staff of Ural Federal District Universities: Qualitative Research - G. E. Zborovsky; P. A. Ambarova; V. S. Katashinskikh; E. V. Kemmet (Высшее образование в России)
The article presents an analysis of the resource capacity of academic community of Ural Federal District universities based on qualitative research data. The main method was conducting 40 semi-structured interviews with Ural universities academic staff. The study used a quota sample, in which informants were differentiated into groups by age (under and over 40) and by the field of scientific knowledge in which they work. The study included an analysis of statistical data reflecting the main indicators of the development of the RPC of the universities of Ural Federal District in the period 2014–2023. As sources of statistical data, databases of monitoring the effectiveness of higher education organizations, data of the Ministry of Science and Higher Education of the Russian Federation, and «Indicators of Education» statistical collection were used. The main results covered five resource blocks of the RPC: socio-demographic, research, pedagogical, the resource of interaction of the RPS and research teams, moral and symbolic. In aggregate and interrelation, 11 types of RPS resources were disclosed. It was concluded that the results of a comprehensive study of the resourcing of the RPC can serve as a basis for management decisions on staffing strategies of universities in new conditions. The strengths and resource deficits of the RPC were shown. The study allowed us to draw conclusions about those resources that have a cross-cutting character (temporal, moral and ideological) and are necessary as predictors of the actualization of other resources (research, publication, pedagogical).